Temperature Effect on Gonads of Freshwater Fish Cyprinus carpio - Gaikwad, Milind V.; Khillare, Prof. Yashwant K. (Asian Journal of Biological and Life Sciences, 2015)
Development of ovary and oocyte along with male gonad testis of the freshwater fishes was observed .When rearing 51 day-old Cyprinius carpio at elevated sub-lethal temperatures to (control), 28 and 34°C (experimental) was exposed no death was observed, but the ovarian dimensions differed significantly (F=5.25cm, DF=3, P < 0.05) as manually measured by image software of contrast phage microscope between the 27°C and 30°C and between 32°C treatments. Observation indicated that numbers of germ cells per ovarian cross-section seemed to be more numerous and dense in 27°C treatment than in either the germ >30°C or 32°C treatments were less dense. Testicular cross-section areas were significantly (T=5.11cm, DF=3, P>0.05), different among all groups at the conclusion of the temperature treatments at 27 °C and 30 °C